DESIGN OF SOCIAL ARITHMETIC LEARNING (NETTO, BRUTO, AND TARA) IN VII GRADE WITH SNACK CONTEXT USING PMRI APPROACH - Reny Shinta Sari; Ratu Ilma Indra Putri; Yusuf Hartono (Sriwijaya University Learning and Education International Conference, 2018)
This research is the kind of design research that has purpose to produce learning path at netto, bruto, tara in seventh grade of junior high school using snack’s context. In this research there are learning instruction series which is designed and developed according to the learning activities assumption that used is Pendidikan Matematika realistik Indonesia (PMRI). This research was done by 22 Junior High School students at VII grade as a research’s subject by producing learning trajectory (LT) that will help the student to find out netto, bruto, tara by the using of activity series at learning process. At the informal stage, as the beginning activity, researcher serves several snacks that will be measured by the student. Next at the preformal stage, student will start to find the common from the activity that they had done. After that student will be able to change to the mathematic sentence as model of. The next stage is model for where student could find the netto, bruto, tara formula so at the formal stage student able to solve the questions that relate to the daily life.